Adiporedoxin, an upstream regulator of ER oxidative folding and protein secretion in adipocytes - Mark P. Jedrychowski; Libin Liu; Collette J. Laflamme; Kalypso Karastergiou; Tova Meshulam; Shi-Ying Ding; Yuanyuan Wu; Mi-Jeong Lee; Steven P. Gygi; Susan K. Fried; Paul F. Pilch (Elsevier, 2015)
Objective: Adipocytes are robust protein secretors, most notably of adipokines, hormone-like polypeptides, which act in an endocrine and paracrine fashion to affect numerous physiological processes such as energy balance and insulin sensitivity. To understand how such proteins are assembled for secretion we describe the function of a novel endoplasmic reticulum oxidoreductase, adiporedoxin (Adrx). Methods: Adrx knockdown and overexpressing 3T3-L1 murine adipocyte cell lines and a knockout mouse model were used to assess the influence of Adrx on secreted proteins as well as the redox state of ER resident chaperones. The metabolic phenotypes of Adrx null mice were characterized and compared to WT mice. The correlation of Adrx levels BMI, adiponectin levels, and other inflammatory markers from adipose tissue of human subjects was also studied. Results: Adiporedoxin functions via a CXXC active site, and is upstream of protein disulfide isomerase whose direct function is disulfide bond formation, and ultimately protein secretion. Over and under expression of Adrx in vitro enhances and reduces, respectively, the secretion of the disulfide-bonded proteins including adiponectin and collagen isoforms. On a chow diet, Adrx null mice have normal body weights, and glucose tolerance, are moderately hyperinsulinemic, have reduced levels of circulating adiponectin and are virtually free of adipocyte fibrosis resulting in a complex phenotype tending towards insulin resistance. Adrx protein levels in human adipose tissue correlate positively with adiponectin levels and negatively with the inflammatory marker phospho-Jun kinase. Conclusion: These data support the notion that Adrx plays a critical role in adipocyte biology and in the regulation of mouse and human metabolism via its modulation of adipocyte protein secretion.